Molecular docking and dynamic simulation studies of pentacyclictriterpenoids from euphorbiaceae Plants with snake venom phospolipase a2 And acostatin proteins - GANDEPALLI PRATAP KUMAR; R.AMOS SAMKUMAR; D.PREMNATH; R.S.DAVID PAULRAJ (International Journal of Pharma and Bio Sciences, 2016)
Health threat due to snake bite is one of the most ignored areas of active research vis-à-vis other domains of human healthcare studies. Fatalities due to snake bite are a major health threat affecting the lives of thousands of people every year in many developing countries. The prevalence of mortality caused by snake bite is taken as one of the serious challenges to solve the problem. The objective of the present study was computational analysis of proteins present in high and low poisonous snakes. Docking of inhibitors (taraxerol, taraxasterol, α-amyrin, β-amyrin, friedeline and oleanolic acid) with PLA2 enzyme from common cobra and acostatin from copper head snake for the identification of amino acid residues is crucial to analyze enzyme-inhibitor interaction. Molecular Docking with protein-inhibitors was performed using Schrodinger 16.2v. Glide score revealed that interaction of PLA2 with taraxerol and oleanolic acid showed a score of -1.43 and -1.74 respectively, whereas acostatin with taraxerol and taraxasterol showed the scores -1.78 and -2.00. The Molecular dynamic (MD) simulation studies were performed for docked complexes using Desmond tool. MD simulation of the complexes revealed stable nature of interactions. The present study identifies the interacting amino acid residues of snake venom proteins with ligands using bioinformatics tools and it will help in the development of a versatile drug in near future for treating snake bite